Non-Retroviral Fossils in Vertebrate Genomes - Horie, Masayuki (Molecular Diversity Preservation International (MDPI), 2011)
Although no physical fossils of viruses have been found, retroviruses are known to leave their molecular fossils in the genomes of their hosts, the so-called endogenous retroviral elements. These have provided us with important information about retroviruses in the past and their co-evolution with their hosts. On the other hand, because non-retroviral viruses were considered not to leave such fossils, even the existence of prehistoric non-retroviral viruses has been enigmatic. Recently, we discovered that elements derived from ancient bornaviruses, non-segmented, negative strand RNA viruses, are found in the genomes of several mammalian species, including humans. In addition, at approximately the same time, several endogenous elements of RNA viruses, DNA viruses and reverse-transcribing DNA viruses have been independently reported, which revealed that non-retroviral viruses have played significant roles in the evolution of their hosts and provided novel insights into virology and cell biology. Here we review non-retroviral virus-like elements in vertebrate genomes, non-retroviral integration and the knowledge obtained from these endogenous non-retroviral virus-like elements.